Preparation method of lithium metal battery based on flame-retardant local high-concentration polymer electrolyte
By using flame-retardant locally high-concentrated polymer electrolyte in lithium metal batteries, the problem of flammability and explosiveness of the electrolyte is solved, the safety and circulation performance of the battery are improved, and the long-term and stable operation of the battery is achieved.
Patent Information
- Application Number
- CN202411699779.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-26
- Publication Date
- 2025-02-18
AI Technical Summary
The electrolytes of existing lithium metal batteries are flammable and explosive, and have safety risks, and it is difficult to take into account both circulation performance and safety.
The preparation method based on flame retardant local high-concentration polymer electrolyte is prepared by free radical polymerization by intrinsic flame retardant polymer as support film, combined with traditional organic solvents and double bond-containing esters as crosslinking agents. Electrolytes with flame retardant properties.
It significantly improves the safety characteristics and electrochemical performance of lithium metal batteries, overcomes the problem of poor interface compatibility of traditional batteries, and prevents positive electrode decomposition under high pressure to ensure long-term operation of the battery.
Smart Images

Figure CN119481322A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of lithium metal battery safety, and in particular relates to a method for preparing a lithium metal battery based on a flame-retardant local high-concentration polymer electrolyte. Background Art
[0002] Lithium metal anode is expected to become the first choice for the core anode material of the next generation energy storage system due to its high theoretical specific capacity and low potential. However, the current chemical and electrochemical stability between the electrode and the electrolyte is poor, which has limited the development of lithium metal batteries to a series of problems such as lithium dendrite growth, SEI layer instability, and high-voltage positive electrode decomposition. Electrolyte engineering is one of the effective ways to break through the above bottlenecks. Among them, the Li in the electrolyte is + The regulation of solvation structure has become a hot topic in the field of electrolyte design. + The solvation structure exhibits a strong coordination ability with the solvent, which will induce the solvent to decompose preferentially and produce an unstable SEI layer rich in organic matter, thereby affecting the electrochemical performance. Therefore, by adopting a weakly coordinated solvent, anions are introduced into the solvation structure to improve the solvation structure. This structure helps to generate an inorganic component-rich SEI layer produced by the decomposition of anions, thereby improving the cycle stability of the battery. However, this type of solvent still uses flammable ester or ether electrolytes as the main solvent, and there are still safety issues caused by the flammability and explosion of liquid electrolytes. At present, the use of flame retardant additives can effectively improve the safety characteristics of batteries, but flame retardant additives will affect the cycle performance of batteries. Therefore, the field of lithium metal battery electrolyte engineering urgently needs to develop a new solvation structure regulation strategy that must simultaneously meet the requirements of ensuring electrode stability, optimizing ionic conductivity, and improving safety. Summary of the invention
[0003] In view of the defects of the current existing electrolytes, the present invention provides a method for preparing a lithium metal battery based on a flame-retardant local high-concentration polymer electrolyte. The electrolyte uses an intrinsic flame-retardant polymer as a support membrane, a traditional organic solvent as a main solvent, a solvent that does not participate in the solvation structure as a diluent, and an ester containing a double bond as a cross-linking agent, and a flame-retardant local high-concentration polymer electrolyte is produced by free radical polymerization. This electrolyte not only overcomes the problem of poor interface compatibility of traditional polymer batteries, but also can be compatible with different positive electrodes at the same time, and the positive electrode does not decompose under high pressure, ensuring long-term operation of the battery. The electrolyte has intrinsic flame retardant properties, which ensures the safety characteristics of the battery to a certain extent, and effectively solves the problem of thermal runaway of high-energy density batteries.
[0004] The specific technical scheme of the present invention is:
[0005] A method for preparing a lithium metal battery based on a flame-retardant locally high-concentration polymer electrolyte, comprising the following steps:
[0006] Step (1) adding a high molecular polymer to a solvent, heating and stirring until completely dissolved, filtering and degassing to obtain an electrospinning solution; the mass fraction of the high molecular polymer in the electrospinning solution is 13% to 25%;
[0007] Step (2) injecting the electrospinning solution obtained in step (1) into the electrospinning solution channel, then adjusting the electrospinning process parameters, receiving it with aluminum foil, placing it at room temperature to allow the solvent in the solution to evaporate, and then drying it, thereby preparing a nanofiber membrane with intrinsic flame retardant properties;
[0008] Step (3) adding lithium salt, diluent, crosslinking agent and catalyst to the ether or ester electrolyte in sequence to prepare a prepolymer solution;
[0009] Step (4) assembles a button cell or a soft-pack cell in the order of a positive electrode, the nanofiber membrane with intrinsic flame retardancy obtained in step (2), the prepolymer solution obtained in step (3), and a negative electrode (Li), and finally packages the cell; allows the prepolymer solution to fully infiltrate the nanofiber membrane at room temperature, and then performs a polymerization reaction, so that the prepolymer solution undergoes free radical polymerization to obtain an integrated lithium metal battery based on a flame retardant locally high-concentration polymer electrolyte.
[0010] Furthermore, the high molecular polymer in step (1) is one or a mixture of two or more of polyarylethersulfoneketone, polyarylethernitrile, polyarylethernitrileketone, polyetheretherketone, polyaryletherketone and polyarylethersulfone;
[0011] Furthermore, the solvent in step (1) is one or a mixture of two or more of N-methylpyrrolidone, dimethyl sulfoxide, N,N-dimethylformamide, N,N-dimethylacetamide, acetone, ethanol, and glycerol;
[0012] Furthermore, the process parameters of electrospinning in step (2) are: voltage of 12-26 kV, distance between needle and receiver of 15-22 cm, and pushing speed of electrospinning solution of 0.5-1.5 mL h -1 , the inner diameter of the needle is 0.15-0.5 mm;
[0013] Furthermore, in step (2), the drying temperature is 60 to 80° C., and the drying time is 24 to 48 hours;
[0014] Furthermore, the volume ratio between the ether or ester electrolyte and the diluent in step (3) is 1:1 to 1:5;
[0015] Furthermore, in step (3), the ether electrolyte is one or a mixture of two or more of ethylene glycol dimethyl ether (DME), tetrahydrofuran (THF), 1,2-dimethoxypropane (DMP), dimethoxymethane (DMM), and dioxolane (DOL);
[0016] Furthermore, in step (3), the ester electrolyte is one or a mixture of two or more of ethylene carbonate (EC), cyclopentane sulfone (TMS), propylene carbonate (PC), diethyl carbonate (DEC), dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), ethyl acetate (EA), and methyl acetate (MA);
[0017] Furthermore, the lithium salt described in the above step (3) is one or a mixture of two or more of lithium hexafluorophosphate (LiPF6), lithium bis(trifluoromethylsulfonyl)imide (LiTFSI), lithium perchlorate (LiClO4), lithium tetrafluoroborate (LiBF4), lithium difluorooxalatoborate (LiDFOB), and lithium dioxalatoborate (LiBOB);
[0018] Furthermore, the diluent described in step (3) is one or a mixture of two or more of bis(2,2,2-trifluoroethyl) ether (BTFE), 1,1,2,2-tetrafluoroethyl 2,2,3,3-tetrafluoropropyl ether (TTE), 1,3,5-trifluorobenzene (TFB), 2,2,2-trifluoroethyl trifluoromethanesulfonate (TFES), and ethoxy(pentafluoro)cyclotriphosphazene (PFPN);
[0019] Furthermore, the cross-linking agent described in step (3) is one or a mixture of two or more of polyethylene glycol diacrylate (PEGDA), pentaerythritol tetraacrylate (PETEA), ethylene glycol dimethacrylate (EGDMA), trimethylolpropane triacrylate (TMPTA), 1,6-hexanediol diacrylate (HDDA), and perfluoroalkylethyl acrylate (PFEA);
[0020] Furthermore, the catalyst described in step (3) is one or a mixture of two or more of lithium hexafluorophosphate (LiPF6), lithium bis(trifluoromethylsulfonyl)imide (LiTFSI), aluminum trifluoromethylsulfonate (Al(TOf)3), azobisisobutyronitrile (AIBN), ammonium persulfate (APS), and potassium persulfate (K2S2O8);
[0021] Furthermore, the mass fraction of the catalyst in step (3) in the electrolyte is 0.1% to 1%;
[0022] Furthermore, the concentration of the lithium salt in the electrolyte in step (3) is 3 to 5 M;
[0023] Furthermore, the mass fraction of the cross-linking agent in step (3) in the electrolyte is 1% to 30%;
[0024] Furthermore, the standing time in step (4) is 6 h to 24 h;
[0025] Furthermore, the polymerization time in step (4) is 1 h to 6 h, and the polymerization temperature is 40° C. to 70° C.;
[0026] Furthermore, the positive electrode material described in the above step (4) is one of lithium manganese oxide (LMO), lithium iron phosphate (LFP), lithium nickel cobalt manganese oxide (NCM), and lithium nickel cobalt aluminum oxide (NCA).
[0027] Beneficial effects of the present invention:
[0028] 1. The present invention uses polymer electrolytes with different solvation structures obtained by adjusting the concentrations of ester or ether electrolytes and diluents, lithium salt concentrations, crosslinking agent content, and catalyst dosage.
[0029] 2. Reduce the interfacial impedance through in-situ polymerization, and use intrinsic flame-retardant polymers as supporting diaphragms to significantly improve the safety characteristics and electrochemical performance of the battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 Schematic diagram of the solvation structure of the intrinsic flame-retardant polymer electrolyte prepared by the process of Example 2.
[0031] Figure 2 This is a graph showing the specific capacity performance of a lithium metal battery based on an intrinsic flame-retardant polymer electrolyte prepared by the processes of Examples 1 to 4 at a current density of 1C.
[0032] Figure 3 This is a charge and discharge curve of a Li / LFP battery assembled based on the electrolyte prepared by the process of Example 5 at a current density of 1C.
[0033] Figure 4 This is the XPS spectrum of the C element in the CEI layer of the Li / LCO battery based on the electrolyte prepared by the process of Example 6 after 10 cycles.
[0034] Figure 5 TEM image of the SEI layer of the battery based on the electrolyte prepared by the process of Example 6 after cycling. DETAILED DESCRIPTION
[0035] The following is a further description of the present invention in conjunction with specific embodiments, and the specific implementation is as follows:
[0036] Example 1
[0037] Dissolve poly(arylethersulfoneketone) in N,N-dimethylformamide and heat and stir to prepare an electrospinning solution with a mass fraction of 13%. Inject the solution into a 10 ml syringe and fix it on the pusher. The voltage is 26 kV, the distance between the needle and the receiver is 15 cm, and the pushing speed of the spinning solution is 0.5 mL h -1 , the inner diameter of the needle is 0.2mm, and it is dried at 60℃ for 48h to obtain a fiber membrane with intrinsic flame retardant properties. DEC and TTE are prepared into a precursor solution in a volume ratio of 1:2, 0.1% AIBN is added as a catalyst, 10% PGEDA is added as a cross-linking agent, and 3M lithium difluorooxalate borate is used as a lithium salt (the concentration of lithium salt is 3M compared to DEC). The solution is stirred until clear and transparent and used as a prepolymer solution. The positive electrode (LFP), intrinsic flame retardant fiber membrane (self-extinguishing will occur during the ignition process, and the residual carbon is high), prepolymer solution, and negative electrode (Li) are assembled into a button battery in this order, and allowed to stand for 6h to allow the prepolymer solution to penetrate evenly inside the diaphragm. It is heated at 40℃ for 6h to prepare a lithium metal battery based on a local high-concentration polyelectrolyte with flame retardant properties. The cycle performance test shows that the battery has a specific capacity of 123mAh g at a current density of 1C. -1 .
[0038] Example 2
[0039] Dissolve poly(arylether nitrile) in a mixed solution of N,N-dimethylacetamide and N,N-dimethylformamide (volume ratio 1:1), heat and stir to prepare an electrospinning solution with a mass fraction of 25%. Inject the solution into a 10ml syringe and fix it on the pusher. The voltage is 20kV, the distance between the needle and the receiver is 22cm, and the pushing speed of the spinning solution is 1.5mL h -1 , the inner diameter of the needle is 0.5mm, and it is dried at 80℃ for 24h to obtain a fiber membrane with intrinsic flame retardant properties. DME and PFPN are prepared into a precursor solution in a volume ratio of 1:2, 1% AIBN is added as a catalyst, 30% PETEA is added as a cross-linking agent, and 3M lithium bis(trifluoromethylsulfonyl)imide is used as a lithium salt (the concentration of lithium salt is 3M compared to DEC), and the solution is stirred until it is clear and transparent, and used as a prepolymer solution for standby. The positive electrode (LFP), the intrinsic flame retardant fiber membrane (self-extinguishing will occur during the ignition process, and the residual carbon is high), the prepolymer solution, and the negative electrode (Li) are assembled into a button battery in this order, and allowed to stand for 24h to allow the prepolymer solution to penetrate evenly inside the diaphragm, and heated at 70℃ for 1h to prepare a lithium metal battery based on a local high-concentration polyelectrolyte with flame retardant properties. The cycle performance test shows that the specific capacity of the battery at a current density of 1C is 148.2mAh g -1The improvement in battery cycle performance is mainly attributed to the use of PFPN as a diluent ( Figure 1 Schematic diagram of the solvation structure), does not enter the first solvation sheath, plays a diluting role, prompting anions to preferentially form a stable inorganic-rich SEI layer at the negative electrode, promotes the effective transmission of lithium ions, and ensures long-term battery cycling.
[0040] Example 3
[0041] Dissolve polyetheretherketone in N,N-dimethylacetamide and heat and stir to prepare an electrospinning solution with a mass fraction of 25%. Inject the solution into a 10ml syringe and fix it on the pusher. The voltage is 12kV, the distance between the needle and the receiver is 19cm, and the pushing speed of the spinning solution is 0.5mL h -1 , the inner diameter of the needle is 0.15mm, and it is dried at 70℃ for 48h to obtain a fiber membrane with intrinsic flame retardant properties. DMM and BTFE are configured into a precursor solution in a volume ratio of 1:4, 1% AIBN is added as a catalyst, 1% PETEA is added as a cross-linking agent, and 5M lithium hexafluorophosphate is used as a lithium salt (the concentration of lithium salt is 5M compared to DMM), and the solution is stirred until it is clear and transparent, and used as a prepolymer solution for standby. The positive electrode (LFP), the intrinsic flame retardant fiber membrane (self-extinguishing will occur during the ignition process, and the residual carbon is high), the prepolymer solution, and the negative electrode (Li) are assembled into a button battery in this order, and allowed to stand for 24h to allow the prepolymer solution to penetrate evenly inside the diaphragm, and heated at 60℃ for 2h to prepare a lithium metal battery based on a local high-concentration polyelectrolyte with flame retardant properties. The cycle performance test shows that the battery has a specific capacity of 135.2mAh g at a current density of 1C. -1 The flame-retardant local high-concentration polymer electrolyte prepared by this method has good flame-retardant properties. It will self-extinguish within 3 seconds during the ignition process. After the second ignition, its electrolyte retains a large amount of residual carbon to ensure the safety of the battery in the event of thermal runaway. In contrast, the PP diaphragm melts within 5 seconds after being ignited again and burns out within 10 seconds.
[0042] Example 4
[0043] Dissolve polyaryletherketone in N-methylpyrrolidone and heat and stir to prepare an electrospinning solution with a mass fraction of 20%. Inject the solution into a 10 ml syringe and fix it on the pusher. The voltage is 15 kV, the distance between the needle and the receiver is 19 cm, and the pushing speed of the spinning solution is 1.5 mL h -1, the inner diameter of the needle is 0.3mm, and it is dried at 70℃ for 36h to obtain a fiber membrane with intrinsic flame retardant properties. DOL and TFB are prepared into a precursor solution in a volume ratio of 1:1, AIBN with a mass fraction of 0.1% is added as a catalyst, a mixed solution of PETEA and TMPTA with a mass fraction of 10% (volume ratio of 1:1) is added as a cross-linking agent, and 5M lithium hexafluorophosphate is used as a lithium salt (the concentration of lithium salt is 5M compared to DOL). The solution is stirred until clear and transparent and used as a prepolymer solution for standby. The positive electrode (LFP), the intrinsic flame retardant fiber membrane (self-extinguishing will occur during the ignition process, and the residual carbon is high), the prepolymer solution, and the negative electrode (Li) are assembled into a button battery in this order, and allowed to stand for 6h to allow the prepolymer solution to penetrate evenly inside the diaphragm. It is heated at 50℃ for 3h to prepare a lithium metal battery based on a local high-concentration polyelectrolyte with flame retardant properties. The cycle performance test shows that the battery has a specific capacity of 150mAh g at a current density of 1C. -1 .
[0044] Figure 2 These are the performance diagrams of Examples 1 to 4, all of which have good specific capacity and meet the normal charge and discharge curve of the battery.
[0045] Example 5
[0046] Dissolve polyetheretherketone in N-methylpyrrolidone and heat and stir to prepare an electrospinning solution with a mass fraction of 15%. Inject the solution into a 10 ml syringe and fix it on the pusher. The voltage is 16 kV, the distance between the needle and the receiver is 18 cm, and the pushing speed of the spinning solution is 1.0 mL h -1 , the inner diameter of the needle is 0.3mm, and it is dried at 60℃ for 24h to obtain a fiber membrane with intrinsic flame retardant properties. DMC and TFB are prepared into a precursor solution in a volume ratio of 1:3, AIBN with a mass fraction of 1% is added as a catalyst, a mixed solution of PETEA and TMPTA with a mass fraction of 5% (volume ratio of 1:3) is added as a cross-linking agent, and 4M lithium perchlorate is used as a lithium salt (the concentration of lithium salt is 4M compared to DMC). The solution is stirred until it is clear and transparent, and it is used as a prepolymer solution for standby. The positive electrode (LFP), the intrinsic flame retardant fiber membrane (self-extinguishing will occur during the ignition process, and the residual carbon is high), the prepolymer solution, and the negative electrode (Li) are assembled into a button battery in this order, and allowed to stand for 10h to allow the prepolymer solution to penetrate evenly inside the diaphragm. It is heated at 60℃ for 2h to prepare a lithium metal battery based on a local high-concentration polyelectrolyte with flame retardant properties. The cycle performance test shows that the specific capacity of the battery at a current density of 1C is 142.3mAh g -1 . Figure 3 This is the charge and discharge curve of the Li / LFP battery. The battery has a lower overpotential, indicating that the lithium ion transmission is faster.
[0047] Example 6
[0048] Polyetheretherketone and polyaryletherketone (at a mass ratio of 1:1) were dissolved in N-methylpyrrolidone and heated and stirred to prepare an electrospinning solution with a mass fraction of 17%. The solution was injected into a 10 ml syringe and fixed on a pusher. The voltage was 15 kV, the distance between the needle and the receiver was 22 cm, and the pushing speed of the spinning solution was 1.0 mL h -1 , the inner diameter of the needle is 0.4mm, and it is dried at 70℃ for 48h to obtain a fiber membrane with intrinsic flame retardant properties. DMC and PFPN are configured into a precursor solution in a volume ratio of 1:5, 0.5% AIBN is added as a catalyst, 10% TMPTA solution is added as a cross-linking agent, and 5M lithium perchlorate is used as a lithium salt (the concentration of lithium salt is 5M compared to DMC). The solution is stirred until clear and transparent and used as a prepolymer solution. The positive electrode (LCO), the intrinsic flame retardant fiber membrane (self-extinguishing will occur during the ignition process, and the residual carbon is high), the prepolymer solution, and the negative electrode (Li) are assembled into a button battery in this order, and allowed to stand for 10h to allow the prepolymer solution to penetrate evenly inside the diaphragm. It is heated at 60℃ for 3h to prepare a lithium metal battery based on a local high-concentration polyelectrolyte with flame retardant properties. The cycle performance test shows that the battery has a specific capacity of 125.8mAh g at a current density of 1C. -1 . Figure 4 This is the sputtering distribution diagram of the C element on the SEI layer on the Li negative electrode after 30 cycles. It can be seen from the figure that with the increase of sputtering depth, the C element content is also increasing, indicating that the organic SEI layer is thicker, which is not conducive to the transmission of ions and the protection of the negative electrode. Figure 5 This is also confirmed by the TEM images.
[0049] Example 7
[0050] Polyaryletherketone and polyarylethersulfoneketone (at a mass ratio of 1:1) were dissolved in N,N-dimethylformamide and heated and stirred to prepare an electrospinning solution with a mass fraction of 20%. The solution was injected into a 10ml syringe and fixed on a pusher. The voltage was 17kV, the distance between the needle and the receiver was 22cm, and the pushing speed of the spinning solution was 1.1mL h -1, the inner diameter of the needle is 0.4mm, and it is dried at 60℃ for 38h to obtain a fiber membrane with intrinsic flame retardant properties. After TMS and PFPN are prepared in a precursor solution at a volume ratio of 1:3, 0.5% AIBN is added as a catalyst, 10% TMPTA solution is added as a cross-linking agent, and 4M lithium perchlorate is used as a lithium salt (the concentration of lithium salt is 4M compared to TMS). The solution is stirred until it is clear and transparent, and it is used as a prepolymer solution for standby. The positive electrode (NCM), intrinsic flame retardant fiber membrane (self-extinguishing will occur during the ignition process, and the residual carbon is high), prepolymer solution, and negative electrode (Li) are assembled into a button battery in this order, and allowed to stand for 10h to allow the prepolymer solution to penetrate evenly inside the diaphragm. It is heated at 50℃ for 3h to prepare a lithium metal battery based on a local high-concentration polyelectrolyte with flame retardant properties. The cycle performance test shows that the specific capacity of the battery at a current density of 1C is 155.2mAh g -1 .
[0051] Example 8
[0052] Dissolve poly(arylether nitrile ketone) in N,N-dimethylformamide and heat and stir to prepare an electrospinning solution with a mass fraction of 18%. Inject the solution into a 10 ml syringe and fix it on the pusher. The voltage is 19 kV, the distance between the needle and the receiver is 20 cm, and the pushing speed of the spinning solution is 1.3 mL h -1 , the inner diameter of the needle is 0.5mm, and it is dried at 60℃ for 36h to obtain a fiber membrane with intrinsic flame retardant properties. After TMS and BTFE are prepared in a precursor solution in a volume ratio of 1:2, 0.3% AIBN is added as a catalyst, 10% EGDMA solution is added as a cross-linking agent, and 2M lithium perchlorate is used as a lithium salt (the concentration of lithium salt is 2M compared to TMS). The solution is stirred until it is clear and transparent and used as a prepolymer solution. The positive electrode (LFP), the intrinsic flame retardant fiber membrane (self-extinguishing will occur during the ignition process, and the residual carbon is high), the prepolymer solution, and the negative electrode (Li) are assembled into a button battery in this order, and allowed to stand for 10h to allow the prepolymer solution to penetrate evenly inside the diaphragm. It is heated at 70℃ for 3h to prepare a lithium metal battery based on a local high-concentration polyelectrolyte with flame retardant properties. The battery has a specific capacity of 133.4mAh g at a current density of 1C. -1 .
Claims
1. A method for preparing a lithium metal battery based on a flame-retardant locally high-concentration polymer electrolyte, characterized in that: Here are the steps: Step (1) adding a high molecular polymer to a solvent, heating and stirring until completely dissolved, filtering and degassing to obtain an electrospinning solution; the mass fraction of the high molecular polymer in the electrospinning solution is 13% to 25%; Step (2) injecting the electrospinning solution obtained in step (1) into the electrospinning solution channel, then adjusting the electrospinning process parameters, receiving it with aluminum foil, placing it at room temperature to allow the solvent in the solution to evaporate, and then drying it, thereby preparing a nanofiber membrane with intrinsic flame retardant properties; Step (3) adding lithium salt, diluent, crosslinking agent and catalyst to the ether or ester electrolyte in sequence to prepare a prepolymer solution; Step (4) assembles a button cell or a soft-pack cell in the order of a positive electrode, the nanofiber membrane with intrinsic flame retardancy obtained in step (2), the prepolymer solution obtained in step (3), and a negative electrode (Li), and finally packages the cell; allows the prepolymer solution to fully infiltrate the nanofiber membrane at room temperature, and then performs a polymerization reaction, so that the prepolymer solution undergoes free radical polymerization to obtain an integrated lithium metal battery based on a flame retardant locally high-concentration polymer electrolyte.
2. The method for preparing a lithium metal battery based on a flame-retardant locally high-concentration polymer electrolyte according to claim 1, characterized in that: The high molecular polymer described in step (1) is one or a mixture of two or more of polyarylethersulfoneketone, polyarylethernitrile, polyarylethernitrileketone, polyetheretherketone, polyaryletherketone and polyarylethersulfone; In step (3), the ether electrolyte is one or a mixture of two or more of ethylene glycol dimethyl ether, tetrahydrofuran, 1,2-dimethoxypropane, dimethoxymethane, and dioxolane; The ester electrolyte in step (3) is one or a mixture of two or more of ethylene carbonate, cyclopentane sulfone, propylene carbonate, diethyl carbonate, dimethyl carbonate, ethyl methyl carbonate, ethyl acetate, and methyl acetate.
3. The method for preparing a lithium metal battery based on a flame-retardant locally high-concentration polymer electrolyte according to claim 1, characterized in that: In step (3), The lithium salt is one or a mixture of two or more of lithium hexafluorophosphate, lithium bis(trifluoromethylsulfonyl)imide, lithium perchlorate, lithium tetrafluoroborate, lithium difluorooxalatoborate, and lithium dioxalatoborate; The diluent is one or a mixture of two or more of bis(2,2,2-trifluoroethyl) ether, 1,1,2,2-tetrafluoroethyl 2,2,3,3-tetrafluoropropyl ether, 1,3,5-trifluorobenzene, 2,2,2-trifluoroethyl trifluoromethanesulfonate, and ethoxy(pentafluoro)cyclotriphosphazene; The crosslinking agent is one or a mixture of two or more of polyethylene glycol diacrylate, pentaerythritol tetraacrylate, ethylene glycol dimethacrylate, trimethylolpropane triacrylate, 1,6-hexanediol diacrylate, and perfluoroalkylethyl acrylate; The catalyst is one or a mixture of two or more of lithium hexafluorophosphate, lithium bis(trifluoromethylsulfonyl)imide, aluminum trifluoromethylsulfonate, azobisisobutyronitrile, ammonium persulfate and potassium persulfate.
4. The method for preparing a lithium metal battery based on a flame-retardant locally high-concentration polymer electrolyte according to claim 1, characterized in that: The solvent described in step (1) is one or a mixture of two or more of N-methylpyrrolidone, dimethyl sulfoxide, N,N-dimethylformamide, N,N-dimethylacetamide, acetone, ethanol, and glycerol.
5. The method for preparing a lithium metal battery based on a flame-retardant locally high-concentration polymer electrolyte according to claim 1, characterized in that: The process parameters of electrospinning in step (2) are: voltage of 12-26 kV, distance between needle and receiver of 15-22 cm, and pushing speed of electrospinning solution of 0.5-1.5 mL h -1 The inner diameter of the needle is 0.15~0.5mm.
6. The method for preparing a lithium metal battery based on a flame-retardant locally high-concentration polymer electrolyte according to claim 1, characterized in that: In step (2), the drying temperature is 60 to 80° C. and the drying time is 24 to 48 hours.
7. The method for preparing a lithium metal battery based on a flame-retardant locally high-concentration polymer electrolyte according to claim 1, characterized in that: The volume ratio between the ether or ester electrolyte and the diluent described in step (3) is 1:1 to 1:
5.
8. The method for preparing a lithium metal battery based on a flame-retardant locally high-concentration polymer electrolyte according to claim 1, characterized in that: In step (3), The mass fraction of the catalyst in the electrolyte is 0.1% to 1%; The concentration of the lithium salt in the electrolyte is 3 to 5 M; The mass fraction of the cross-linking agent in the electrolyte is 1% to 30%.
9. The method for preparing a lithium metal battery based on a flame-retardant locally high-concentration polymer electrolyte according to claim 1, characterized in that: In step (4), the standing time is 6 h to 24 h; the polymerization time is 1 h to 6 h, and the polymerization temperature is 40° C. to 70° C.
10. The method for preparing a lithium metal battery based on a flame-retardant locally high-concentration polymer electrolyte according to claim 1, characterized in that: In step (4), the positive electrode material is one of lithium manganese oxide, lithium iron phosphate, lithium nickel cobalt manganese oxide, and lithium nickel cobalt aluminum oxide.